Revisiting the Poetics and Politics of Modernism
XIII, 297 p. 8 illus.
Keywords: This book revisits women’s literature in 1922, long hailed as the miracle year of literary modernism, a landmark year of avant-garde innovations in publications that included James Joyce’s Ulysses, T. S. Eliot’s The Waste Land, and Ezra Pound’s The Cantos. Yet if 1922 has been considered a modernist annus mirabilis, it was many things besides. In “1922 or thereabouts,” according to Willa Cather, the literary “world broke in two,” sequestering traditional writers from those considered modern. Many women writers produced work that year across a spectrum of genres, forms, and politics that would not be accepted into Hugh Kenner’s modernist canon. Nor, however, did they readily fit into Cather’s categories, in some cases rupturing, and in other cases affirming a consensus of modernism as a masculinist, culturally imperialist interwar enterprise. Considering 1922’s historical significance, the essays in this collection seek greater inclusion of women in our memory of this year, including writers from a range of global and regional contexts and cultural backgrounds. Extending other attempts to examine the gender politics of modernism/modernity over the past thirty years, the project draws connections between the significance of 1922, as it has been understood in the new modernist studies, and feminist literary criticism that utilizes single-year approaches, to revisit and reflect on women’s history and the gender politics of modernism. Tamlyn Avery is Senior Lecturer in English Literature at Adelaide University, Australia, and a senior research fellow in American Studies at the University of Queensland.Specializing in nineteenth and twentieth-century U.S. literature and modernism, she is author of The Regional Development of the American Bildungsroman, 1900–1960 (2023), and an editor of the Australasian Modernist Studies Association’s journal, Affirmations: of the Modern. She has published extensively on American and African American Literature, modernism, and modern women’s writing and poetry in PMLA, Modernism/modernity, American Literature, the African American Review, and elsewhere. Sascha Morrell is Lecturer in Literary Studies at Monash University, Australia. She has published widely on U.S. and modernist literatures, including chapters in The Cambridge History of the Australian Novel (2023) and The Oxford Handbook of George Orwell (2025). Sascha’s research has also examined Australian literature in transnational contexts, the overlap between competing constructions of “the south” globally, and the appropriation of Haitian history and cultural motifs (including the zombie) in modern U.S. fiction, theatre, and film. .